Carbohydrates and Amino Compounds as Short‐Term Indicators of Soil Management. Issue 1 (23rd November 2016) - Abdelrahman, Hamada; Cocozza, Claudio; Olk, Daniel C.; Ventrella, Domenico; Miano, Teodoro
Abstract : The objective of this work was to evaluate the suitability of carbohydrates and amino compounds in soil and soil organic matter (SOM) fractions to depict the management‐induced changes in soil over short‐term course. Soil samples were collected from two experimental fields managed according to organic farming regulations and a sequential fractionation procedure was applied to separate the light fraction (LF), particulate organic matter (POM), and mobile humic acid (MHA). Contents of carbohydrates and amino compounds were determined in soil and correspondent SOM fractions. Over a 2‐year course, carbohydrate contents decreased in the LF fraction while it increased noticeably in the POM and slightly in the MHA fractions leading into questioning whether decomposing materials get incorporated into older fractions. Amino N content constituted up to 30% of total soil N, with a major contribution of the humic fraction (MHA). Although the LF, POM, and MHA fractions showed the greatest amino N content after the compost‐legumes combinations, the carbohydrate and amino N contents in the POM and MHA fractions of the unamended soil increased as large as the corresponding fertilized plots, underlining that conservative soil management results in accumulation of labile forms of soil C and N that consequently might build up soil fertility. The changes after different treatments suggest the suitability of carbohydrates and amino compounds as short‐term indicators for soil management. Abstract : The light fraction (LF), the particulate organic matter, the mobile humic acid are labile soil organic matter (SOM) fractions. Fractional changes, over 2‐year course, indicate these fractions are better suited to reveal SOM responses to short‐term management than total SOM.